Computational design of water-soluble analogues of the potassium channel KcsA - Slovic, Avram M. (National Academy of Sciences, 2004)
Although the interiors of membrane and water-soluble proteins are similar in their physicochemical properties, membrane proteins differ in having larger fractions of hydrophobic residues on their exteriors. Thus, it should be possible to water-solubilize membrane proteins by mutating their lipid-contacting side chains to more polar groups. Here, a computational approach was used to generate water-soluble variants of the potassium channel KcsA. As a probe of the correctness of the fold, the proteins contain an agitoxin2 binding site from a mammalian homologue of the channel. The resulting proteins express in high yield in Escherichia coli and share the intended functional and structural properties with KcsA, including secondary structure, tetrameric quaternary structure, and tight specific binding to both agitoxin2 and a small molecule channel blocker.